Risk factors for development of covid associated pulmonary aspergillosis in ICU population. An observational study from a large tertiary care hospital - Iqbla, Ahtesham; Hassan, Muahmmad Rauf-ul-; Waseem, Muhammad; Ashraf, Muhammad Zubair; Abaid, Tehreem; Saleem, Anam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Covid associated pulmonary aspergillosis is a serious life-threatening infection which is increasingly being identified in severe covid pneumonia. There are multiple factors which predispose to this infection, still lot of research is needed to explore more about this infection Objective: Our aim of study was to find out risk factors associated with development of CAPA in severe covid pneumonia. Materials and methods: We prospectively enrolled 698 cases of severe covid pneumonia and aimed to identify risk factors associated with development of CAPA. We included only those who were PCR confirmed cases severe covid pneumonia requiring ICU admission with at least 48 hours of ICU stay. Infectious disease experts decided candidacy of Tocilizumab. CAPA cases were diagnosed according to ISHAM criteria for diagnosis of CAPA. Results: Out of 678 participants, 17.4% developed CAPA. Out of 17.4% cases of CAPA, 83.9% did not survive. Median ICU stay was 10 days. NUTRIC score and ICU days were identified as statistically significant risk factors for CAPA (OR: 2.1,1.2 p= 0.006, <0.001). Median NUTRIC score was 3. Tocilizumab prevents development of CAPA (OR: 0.09, p=< 0.001). Conclusion: We concluded that NUTRIC score and ICU days are predisposing factors for CAPA in severe covid pneumonia. Tocilizumab has role in reducing CAPA infection in severe covid pneumonia.